Building back better? The role of education sector responses in strengthening or eroding societal resilience during the COVID-19 pandemic - Shah, Ritesh; Flemming, Jennifer; Chinnery, Julie; Heaner, Gwen (Frontiers in Education, 2024)
COVID-19 laid bare many failings and shortcomings of state systems, institutions and structures which aim to protect citizens against harm. As observed from the outcomes of the pandemic in many parts of the Global South and Global North, the resilience of health, social protection, governance, economic, education, and social welfare systems has been significantly eroded or challenged, leaving large segments of the population open to heightened risk and vulnerability. This has been noted to have significantly eroded social capital, namely the trust, communication, and dialogue between citizens in the state as well as citizens with each other. Based on comparative research carried out on the return to schooling process in five countries, Lebanon, Nigeria, Colombia, Georgia, and Zambia, the paper highlights the important role and function that educational governance, decision-making, and control throughout the pandemic has played a key role in either maintaining or erode social capital, and ultimately the resilience of the entire education system. Much of this was based on how well state officials and local education officials both considered and communicated their actions to educators, students and their families. The importance of education as a site where both bridging and linking social capital is both strengthened, but also capitalized on is also discussed. Specifically, the paper highlights, using the example of COVID-19 education responses, how a state that is responsive and accountable to its citizenry in a time of crisis, stands the greatest chance of ensuring such periods do not lead to an erosion of social capital.